Flexible aluminum anode and flexible aluminum air power supply
By forming an aluminum-zinc alloy layer on the surface of flexible metal aluminum, the problem of limited application and self-corrosion of aluminum air power supply in the field of flexible electronics is solved, and efficient and low-cost preparation of flexible aluminum air power supply is achieved, which is suitable for flexible electronic equipment.
Patent Information
- Application Number
- CN202411935092.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The application of existing aluminum air power supplies in the field of flexible electronics is limited by their rigid structure and self-corrosion problems, and the preparation process of the prior art is complex and costly.
Flexible aluminum anode is prepared by adding zinc chloride to its surface and alloying reaction under heating conditions to form an aluminum-zinc alloy layer. This method is simple and easy to use and is suitable for large-scale industrial production.
The aluminum-zinc alloy layer of the flexible aluminum anode alleviates the problem of self-corrosion, improves the power generation efficiency of the power supply, and the preparation method reduces energy consumption and production costs, and is suitable for flexible electronic equipment.
Smart Images

Figure CN119673942A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air power sources and relates to a flexible aluminum anode and a flexible aluminum air power source. Background Art
[0002] Fossil energy is becoming increasingly depleted and environmental problems are becoming increasingly prominent. There is an urgent need to find a new type of energy conversion system that is efficient and environmentally friendly to meet the country's supply needs. At present, metal-air power supply technology has been gradually developed and promoted due to its economical price, high energy density, safety and reliability, and can show unique application advantages in emergency, communication and other fields.
[0003] With the rapid development of flexible electronic devices, there is an urgent need for flexible energy products that match them. The energy density of aluminum is 8.2Wh / g, which is higher than anode materials such as lithium, magnesium, and zinc, and the theoretical specific capacity of aluminum is as high as 2978mAh / g, second only to lithium. All these show that aluminum is an excellent anode material for air power sources. However, the rigid structure of aluminum-air power sources limits its application in the field of flexible electronics. Therefore, deformable power sources that can be bent, twisted, rolled up or stretched to a certain extent and still maintain their original functions are a new development direction for aluminum-air power sources. In addition, when metal aluminum is used alone as an anode, severe self-corrosion reactions will occur, and insoluble byproducts will also be generated on its surface, thereby passivating the electrode activity, which limits the development of aluminum-air power sources.
[0004] Prior art patent document CN 111682182A discloses a new type of printable flexible paper-based aluminum-air power source, which consists of an aluminum ink anode, a carbon ink cathode, and a paper substrate. The aluminum ink anode and the carbon ink cathode are respectively covered on both sides of the paper substrate, and liquid alloy particles are added to the aluminum ink anode. The aluminum ink anode is activated by adding liquid alloy particles. The liquid alloy particles are composed of two or more of Ga, In, Sn, Bi, and Zn, and there are many types and the preparation process is complicated.
[0005] Prior art patent document CN 109494431 A discloses a bendable flexible aluminum-air power source, which includes an aluminum alloy anode, an alkaline hydrogel electrolyte, an air cathode using a composite catalyst, and a cathode current collector from the inside out. The document first sandwiches the prepared aluminum alloy anode in the middle, and places an alkaline hydrogel electrolyte, an air cathode using a composite catalyst, and a cathode current collector on both sides from the inside out. The document sandwiches the aluminum alloy anode in the middle to prevent surface passivation. The material of the aluminum alloy anode in the document is composed of 97~99% aluminum, 0.5~1% magnesium, 0.1~1.0% gallium, and 0.1~1.0% indium, which has a complex composition and is not easy to prepare continuously.
[0006] Prior art patent document CN 116937023 A discloses a high-performance fiber-shaped flexible aluminum-air power source and a preparation method. The battery in the document includes a flexible hydrogel electrolyte, a flexible positive electrode and a spring-shaped aluminum wire flexible negative electrode. The flexible hydrogel electrolyte in the document is an alkaline electrolyte containing a xylitol additive, wherein the concentration of the alkali is 2~6mol / L, the concentration of xylitol is 1~3mol / L, and 300~900μL of alkaline electrolyte is dipped per 1cm gelatin hydrogel. The document uses a modified electrolyte to solve the problem of hydrogen evolution caused by corrosion of the aluminum negative electrode, but the cost of the electrolyte is high, which is not conducive to large-scale promotion.
[0007] In summary, there is an urgent need to develop a flexible aluminum anode and a simple and low-cost production method to meet the needs of the flexible electronics field. Summary of the invention
[0008] Based on this, the object of the present invention is to provide a flexible aluminum anode, which can be used in a flexible aluminum air power source.
[0009] The invention also provides a method for preparing the anode, a flexible aluminum-air power source, and application of the flexible aluminum-air power source on flexible equipment.
[0010] To achieve the above object, the present invention adopts the following technical solutions: The invention provides a flexible aluminum anode, the surface of which is provided with an aluminum-zinc alloy layer.
[0011] Furthermore, the aluminum-zinc alloy layer is obtained by adding zinc chloride on the surface of the flexible metal aluminum, and under heating conditions, the zinc chloride and the flexible metal aluminum undergo an alloying reaction.
[0012] The present invention further provides an application of a flexible aluminum anode in a flexible aluminum-air power source.
[0013] The present invention further provides a flexible aluminum-air power source, comprising an anode, a cathode and an electrolyte, wherein the anode comprises the flexible aluminum anode.
[0014] Furthermore, the cathode includes a mixture of manganese oxide and carbon, and the electrolyte includes polyacrylic acid gel mixed with potassium hydroxide.
[0015] The present invention further provides an application of a flexible aluminum-air power source on a flexible device, wherein the flexible device includes a flexible watch, an intelligent flexible sensor or a flexible outdoor power source.
[0016] The present invention further provides a method for preparing a flexible aluminum anode, wherein the flexible metal aluminum is installed on a rotating shaft, the flexible metal aluminum is driven by the rotating shaft for transmission, the zinc chloride is spread on the surface of the flexible metal aluminum during transmission, and the transmission rate and heating temperature are controlled.
[0017] Furthermore, the transfer rate is positively correlated with the heating temperature.
[0018] Furthermore, the conveying rate is 5-20 cm / h, and the heating temperature is ≥283°C; in order to reduce energy consumption and save costs, the preferred heating temperature is 283-300°C.
[0019] Furthermore, the amount of zinc chloride added is controlled according to the surface area of the flexible aluminum metal, and the amount added is less than 1.63 g / cm 2 The flexible metal aluminum includes metal aluminum strip, metal aluminum wire or braided aluminum rope, preferably metal aluminum strip, the thickness of the metal aluminum strip is 8-2000μm, and the purity is greater than 99.9%; the zinc chloride is in powder form.
[0020] The beneficial effects of the present invention are: 1. The flexible aluminum anode provided by the present invention can be applied to a flexible aluminum-air power source. The aluminum-zinc alloy layer on its surface can alleviate the self-corrosion problem of pure metal aluminum when used as the anode of the aluminum-air power source. Its microstructure is dense and its specific surface area is large, which can effectively improve the power generation efficiency of the power source.
[0021] 2. The method for preparing a flexible aluminum anode provided by the present invention adopts flexible metal aluminum (metal aluminum strip, metal aluminum wire or braided aluminum rope) as the base material, which can realize a continuous preparation process, is simple and easy, and can meet the needs of large-scale industrial production.
[0022] 3. The flexible aluminum-air power source containing a flexible aluminum anode provided by the present invention can be widely used in flexible devices including flexible watches, smart flexible sensors or flexible outdoor power sources. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Attached Figure 1 Schematic diagram of the preparation process of flexible aluminum anode; Attached Figure 2 This is the XRD spectrum of the metallographic structure of the aluminum-zinc alloy layer on the surface of the flexible aluminum anode; Attached Figure 3 This is the SEM image of the surface morphology of the aluminum-zinc alloy layer on the surface of the flexible aluminum anode; Attached Figure 4This is the SEM surface scanning element distribution diagram of the aluminum-zinc alloy layer on the surface of the flexible aluminum anode; Figure a is the Al element, Figure b is the Cl element, Figure c is the yellow Cl element, the red Zn element, the blue Al element, and d is the morphology diagram; Attached Figure 5 This is a test process diagram of the corrosion resistance of flexible aluminum anode; Attached Figure 6 This is the test result of the corrosion resistance of the flexible aluminum anode; Attached Figure 7 This is a performance test diagram of flexible aluminum air power supply. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. The embodiments mentioned are all implemented on the premise of the technical solutions of the present invention, and detailed implementation processes are given, but it should be stated that the protection scope of the present invention is not limited to the following embodiments. Example
[0026] The process of preparing the flexible aluminum anode in the present invention is as follows: Figure 1 shown.
[0027] First, the flexible aluminum metal is installed on the rotating shaft as the base material, and the flexible aluminum metal is transported by the rotating shaft. During the transportation process, zinc chloride powder is spread on the surface of the flexible aluminum metal, and then it is transported to the top of the heating table and heated. The heating temperature is controlled to be higher than the melting point of zinc chloride, that is, 283°C, so that the zinc chloride is hot-melted and reacts with the flexible aluminum metal to form an alloy. The reaction is: ((2x+3) / 3)Al + xZnCl2=AlZn x + (2x / 3) AlCl3. Since the heating reaction temperature is higher than the sublimation temperature of aluminum chloride, an aluminum-zinc alloy layer can be formed in situ on the surface of the flexible metal aluminum after the aluminum chloride sublimates. This preparation method can realize a quantitative and continuous preparation process. The flexible metal aluminum structure in the present invention is flexible and has no size restrictions. It can be made of metal aluminum strips, metal aluminum wires, or braided metal aluminum ropes; the thickness of the alloy layer is not restricted, and the thickness of the alloy layer can be quantitatively controlled by controlling the amount of zinc chloride added and the transmission speed according to the requirements of the electrochemical performance of the flexible aluminum-air power source. In this embodiment, a metal aluminum strip with a thickness of 500μm and a purity of >99.9% is used as the base material. The amount of zinc chloride raw material added is determined based on the area of the base material. The amount of zinc chloride added in this embodiment is 1.5g / cm 2 , set the conveying rate to 10 cm / h and the heating temperature to 283°C.
[0028] The surface phase structure of the prepared flexible aluminum anode was tested by X-ray diffraction. The test results are as follows: Figure 2As shown. Figure 2 It can be seen that new diffraction peaks appear between 2θ=37° and 45° in the figure, which correspond to the diffraction peaks of zinc in the zinc-aluminum alloy, respectively, indicating that the preparation method provided by the present invention realizes the process of in-situ preparation of aluminum-zinc alloy on flexible metal aluminum.
[0029] The surface morphology and element distribution of the prepared flexible aluminum anode were tested by electron microscopy. The test results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the aluminum-zinc alloy layer on the surface of the flexible aluminum anode has a dense microstructure, a porous coral reef-like structure, and a large specific surface area. Figure 4 It can be further explained that the Zn element is evenly dispersed on the surface of the flexible aluminum anode, and the residual amount of Cl element is small.
[0030] The corrosion resistance of flexible aluminum anodes was tested, such as Figure 5 As shown, pure aluminum and the flexible aluminum anode block of the present invention of the same size are placed in a 0.5 mol / L sodium hydroxide solution respectively. It can be clearly seen that pure aluminum will continuously precipitate gas (the arrows indicate the precipitated bubbles), and the side reaction is violent. This shows that the flexible aluminum anode obtained by the preparation method provided by the present invention has excellent corrosion resistance, and when used as an anode material of an air power source, the service life of the air power source can be greatly improved.
[0031] In order to further illustrate the difference in corrosion between pure aluminum and the flexible aluminum anode of the present invention in alkaline solution, the anode was taken out and photographed after being immersed in 0.5 mol / L sodium hydroxide solution for 20 hours. Figure 6 As shown, the surface of pure aluminum metal has obvious corrosion marks, while the surface of the flexible aluminum anode has no obvious changes. This shows that the flexible aluminum anode obtained by the preparation method provided by the present invention exhibits excellent alkaline corrosion resistance and slows down the hydrogen evolution reaction.
[0032] Pure aluminum and the flexible aluminum anode of the present invention were used as anodes, a mixture of manganese oxide and carbon was used as cathode, and a polyacrylic acid gel mixed with 4 mol / L potassium hydroxide was used as electrolyte to assemble a flexible aluminum-air power source. The anode specific capacity of the flexible aluminum-air power source was tested at a current density of 10 mA / cm 2 , the test results are as follows Figure 7 As shown. Figure 7 It can be seen that compared with pure metallic aluminum, when the flexible aluminum anode is used as the anode, the discharge specific capacity of the aluminum-air power source is increased from 660mAh / g to 800mAh / g, an increase of more than 20%.
[0033] In summary, the flexible aluminum anode provided by the present invention can be applied to a flexible aluminum-air power source. The aluminum-zinc alloy layer on its surface can alleviate the self-corrosion problem of pure metal aluminum when used as the anode of the aluminum-air power source. Its microstructure is dense and its specific surface area is large, which can effectively improve the power generation efficiency of the power source. The method for preparing a flexible aluminum anode provided by the present invention uses flexible metal aluminum (metal aluminum strip, metal aluminum wire or braided aluminum rope) as a base material, which can realize a continuous preparation process, is simple and easy, and can meet the needs of large-scale industrial production. The flexible aluminum-air power source provided by the present invention can be widely used in flexible devices including flexible watches, smart flexible sensors or flexible outdoor power sources.
[0034] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A flexible aluminum anode, characterized in that: The surface of the flexible aluminum anode is provided with an aluminum-zinc alloy layer.
2. The flexible aluminum anode according to claim 1, characterized in that: The aluminum-zinc alloy layer is obtained by adding zinc chloride on the surface of the flexible metal aluminum, and under heating conditions, the zinc chloride reacts with the flexible metal aluminum to form an alloy.
3. Use of the flexible aluminum anode described in claim 1 or 2 in a flexible aluminum-air power source.
4. A flexible aluminum air power source, characterized in that: The invention comprises an anode, a cathode and an electrolyte, wherein the anode comprises the flexible aluminum anode according to claim 1 or 2.
5. The flexible aluminum-air power source as claimed in claim 4, characterized in that: The cathode includes a mixture of manganese oxide and carbon; the electrolyte includes polyacrylic acid gel mixed with potassium hydroxide.
6. Application of the flexible aluminum-air power source according to claim 4 or 5 on flexible equipment, characterized in that: The flexible device includes a flexible watch, an intelligent flexible sensor or a flexible outdoor power source.
7. A method for preparing the flexible aluminum anode according to claim 1 or 2, characterized in that: The flexible metal aluminum is mounted on a rotating shaft, and the flexible metal aluminum is driven by the rotating shaft to be transported. The zinc chloride is spread on the surface of the flexible metal aluminum being transported, and the transport rate and the heating temperature are controlled.
8. The preparation method according to claim 7, characterized in that: The transfer rate is positively correlated with the heating temperature.
9. The preparation method according to claim 7, characterized in that: The conveying rate is 5-20 cm / h, and the heating temperature is ≥283°C.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The amount of zinc chloride added is controlled according to the surface area of the flexible aluminum metal, and the amount added is less than 1.63 g / cm 2 The flexible aluminum metal includes an aluminum metal strip having a thickness of 8-2000 μm and a purity of >99.9%; the zinc chloride is in powder form.
Citation Information
Patent Citations
Bendable flexible aluminum air battery
CN109494431A
Printable novel flexible paper-based aluminum air battery
CN111682182A
High-performance fibrous flexible aluminum air battery and preparation method thereof
CN116937023A